Synthesis and Characterization of ZnO Nanoparticles Prepared in Gelatin Media - Zak, A.K.; Abd Majid, Wan Haliza; Darroudi, M.; Yousefi, R. (2011)
Zinc oxide nanoparticles (ZnO NPs) were synthesized via the sol-gel method in gelatin media Long-chain gelatin compounds were utilized to terminate the growth of ZnO-NPs and to stabilize them The ZnO-NPs were characterized by a number of techniques such as X-ray diffraction analysis (XRD) Fourier transform infrared spectroscopy (FTIR) and high-magnification transmission electron microscopy (TEM) The ZnO-NPs calcined at different temperatures exhibited a hexagonal (wurtzite) structure with sizes from 30 to 60 nm The influence of the calcination temperature on the morphology of ZnO-NPs was also investigated The results showed that gelatin is an interesting material that can be used as a stabilizer in the sol-gel technique for preparing small ZnO-NPs (C) 2010 Elsevier B V All rights reserved